Quels tuteurs informatisés pour réduire les comportements d'évitement de la recherche d'aides des apprenants ? - Julie Mulet; Jean-Christophe Sakdavong; Nathalie Huet (Centre National d'Enseignement à Distance, 2017)
Help-seeking may be perceived as a threat for self-esteem and/or for the need of help. Those perceptions may result in help-avoidance despite the need of help. In order to assist help-seeking, we designed a metacognitive tutor which intervenes after a diagnosis of perceived threats of help-seeking. When help-seeking avoidance occurs and if the motivational diagnosis reveals perception of threats, the prompt formulation is designed to reduce these threats. This metacognitive-motivational tutor (MM) is compared to a solely metacognitive tutor (M) (which intervenes without motivational diagnosis) and a condition without tutor (control group). The study was conducted with 214 students. The results show that the MM tutoring condition leads learners to less perceive the act of seeking help as a threat to their competency and autonomy than the conditions of M tutoring and the neutral condition. In addition, compared to the M-tutor, the MM tutor leads to less help avoidance when the tutor is no longer in action. However, there is no difference with the control group. The theoretical and practical implications of these results are discussed.